Environmental planning strategies for optimum solid waste landfill diting - Sumiani Y,; Onn C.C,; Mohd Din M.A,; Wan Jaafar W.Z, (Universiti Kebangsaan Malaysia, 2009)
The use of environmental planning tools for optimum solid waste landfill siting taking into account all environmental implications was carried out by applying Life Cycle Analysis (LCA) to enhance the research information obtained from initial analysis using Geographical Information Systems (GIS). The objective of this study is to identify the most eco-friendly landfill site by conducting a LCA analysis upon 5 potential GIS generated sites which incorporated eleven important criteria related to the social, environmental, and economical factors. The LCA analysis utilized the daily distance covered by collection trucks among the 5 selected landfill sites to generate inventory data on total energy usage for each landfill sites. The planning and selection of the potential sites were facilitated after conducting environmental impact analysis upon the inventory data which showed the least environmental impact.